PERANAN KURIKULUM LPTK BERBASIS KKNI DI PERGURUAN TINGGI - Ella Dewi Latifah; Muhamad Habaib; Lisnawati; Hendi Suhendraya Muchtar; Rita Sulastini (STAI Pelabuhan Ratu, 2022)
Higher education is the highest level of the education system, where graduates of undergraduate programs are expected to be competent and ready to work. Universities have a strategic role and great responsibility in the process of developing quality Indonesian human resources. Therefore, KKNI is used as a reference in creating learning outcomes for graduates of all levels of education at the national level. To achieve this, all universities refer to the KKNI in making or developing higher education curricula. The application of the curriculum that refers to the KKNI aims to clarify how individuals or graduates have a profile and learning outcomes that are expected and will be achieved by students after attending lectures. This paper aims to examine the implementation of the IQF-Based Curriculum in Higher Education. The method used in this research is descriptive analysis method based on literature review or library research. The results of the study show that the implementation of the IQF-based curriculum has a significant impact both for lecturers as educators and for students, especially in improving skills and forming a better attitude. Based on this, the IQF curriculum is good to implement.